Implementation of the online learning during Covid-19: Between obligations and barriers - Mukarromah, Ummi; Wijayanti, Wiwik (Jurnal Pendidikan Vokasi, 2021)
Vocational schools are no exception to implementing the online learning policy during the covid-19 pandemic, including students majoring in hotel accommodation. This study describes how the school develops its readiness to implement the policy, particularly its challenges. This study also aims to determine the constraints and impacts of implementing the policy.  Using a qualitative method, this study involved two vocational schools in Yogyakarta that have a hotel accommodation field. The head of the departments, the productive teachers, and some students was invited to several interviews. Documentation was also used to obtain detailed information. The results were categorized into two aspects: hard skills and soft skills. From the first aspect, challenges faced as the policy's impact are: 1.) Online learning at vocational schools majoring in hotel accommodation requires facilities and infrastructure that do not include internet quota; 2.) Teacher digital competence and teacher creativity in carrying out learning needs to be improved; 3.) Students feel bored with online learning, so motivation needs to be grown; and 4.) Skills/ practice-based learning implemented in school alternately with a limited number of students. The second aspect indicated that the policy makes it difficult to develop students' soft skills that are also measured as the learning objective. These constraints are important to note for the implementation of the online learning policy to be successful.